Thrombotic antiphospholipid syndrome shows strong haplotypic association with SH2B3-ATXN2 locus. - Eguzkine Ochoa (Public Library of Science (PLoS), 2013)
Background Thrombotic antiphospholipid syndrome is defined as a complex form of thrombophilia that is developed by a fraction of antiphospholipid antibody (aPLA) carriers. Little is known about the genetic risk factors involved in thrombosis development among aPLA carriers. Methods To identify new loci conferring susceptibility to thrombotic antiphospholipid syndrome, a two-stage genotyping strategy was performed. In stage one, 19,000 CNV loci were genotyped in 14 thrombotic aPLA+ patients and 14 healthy controls by array-CGH. In stage two, significant CNV loci were fine-mapped in a larger cohort (85 thrombotic aPLA+, 100 non-thrombotic aPLA+ and 569 healthy controls). Results Array-CGH and fine-mapping analysis led to the identification of 12q24.12 locus as a new susceptibility locus for thrombotic APS. Within this region, a TAC risk haplotype comprising one SNP in SH2B3 gene (rs3184504) and two SNPs in ATXN2 gene (rs10774625 and rs653178) exhibited the strongest association with thrombotic antiphospholipid syndrome (p-value = 5,9 × 10(-4) OR 95% CI 1.84 (1.32-2.55)). Conclusion The presence of a TAC risk haplotype in ATXN2-SH2B3 locus may contribute to increased thrombotic risk in aPLA carriers.